Allelopathic effect of walnut leaf extracts on germinating grain amaranth (Amaranthus hypocondriacus) seeds in western Himalayan agri-silviculture system - ABHISHEK BAHUGUNA; PUSHKAR SINGH BISHT; BIRENDRA PRASAD (Seed Research, 2026)
The effects of walnut leaf extracts on grain amaranth (Amaranthus hypocondriacus) cv Prai seed germination and post-germination seedling growth were investigated. Walnut leaf extract was prepared by keeping the crushed dried leaves in distilled water. Seed germination, seedling elongation and weight were determined on the date of final count, however, other seedling vigour ie. vigour index, speed of germination index, relative growth index (RGI), mean daily germination (MDG), mean germination time (MGT) and time to 50% germination (Ts) were calculated as per their respective formulae. There was a significant reduction in seed germination and seedling vigour as an effect of treatment of walnut leaf extracts on grain amaranth. However, MGT and T increased as the leaf extract concentration increased and was found to be lowest in the control. It was found that seed germination and seedling vigour of grain amaranth were affected negatively by walnut leaf extracts in concentration dependent manner.